1986
DOI: 10.1042/bj2390769
|View full text |Cite
|
Sign up to set email alerts
|

Modification of human haemoglobin with glucose 6-phosphate enhances tetramer-dimer subunit dissociation

Abstract: Studies using equilibrium gel-permeation chromatography demonstrate that formation of the covalent adduct of D-glucose 6-phosphate (G6P) with human haemoglobin promotes dissociation of the haemoglobin tetramer into its component alpha beta dimer pairs [Kdoxy = 2.57 X 10(-6) versus Kdoxy (G6P) = 11.22 X 10(-6) M-haem]. On the other hand, Kd for glucosylated haemoglobin is identical with those of the O2- and CO-liganded forms of intact haemoglobin A0. These data are consistent with the phosphate moiety alone bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For example, the native oxy Hb (0.1 mM) maintains a tetrameric structure between pH 7.1 and 7.4 in a phosphate buffer . It dissociates in the presence of 0.5–1.0 M MgCl 2 . , Generally, native Hb maintains tetrameric structures over the concentration of 0.1 mM at pH 7.4 and dissociates at lower concentrations such as 5 μM . Reportedly, PEGylation promotes dissociation of the α 2 β 2 tetramer. ,, An earlier study demonstrated that the dissociation constants of α 2 β 2 tetramer into dimers ( K d ) are 8.5 μM for native Hb, 10.5 μM for 5 kDa bis-PEGylated Hb, and 43.2 μM for 5 kDa multiple-PEGylated Hb with 6 PEG chains in the average (hexa-PEGylated-Hb), although it was not described how the K d values were measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the native oxy Hb (0.1 mM) maintains a tetrameric structure between pH 7.1 and 7.4 in a phosphate buffer . It dissociates in the presence of 0.5–1.0 M MgCl 2 . , Generally, native Hb maintains tetrameric structures over the concentration of 0.1 mM at pH 7.4 and dissociates at lower concentrations such as 5 μM . Reportedly, PEGylation promotes dissociation of the α 2 β 2 tetramer. ,, An earlier study demonstrated that the dissociation constants of α 2 β 2 tetramer into dimers ( K d ) are 8.5 μM for native Hb, 10.5 μM for 5 kDa bis-PEGylated Hb, and 43.2 μM for 5 kDa multiple-PEGylated Hb with 6 PEG chains in the average (hexa-PEGylated-Hb), although it was not described how the K d values were measured.…”
Section: Discussionmentioning
confidence: 99%
“…27 It dissociates in the presence of 0.5−1.0 M MgCl 2 . 35,36 Generally, native Hb maintains tetrameric structures over the concentration of 0.1 mM at pH 7.4 37 and dissociates at lower concentrations such as 5 μM. 38 Reportedly, PEGylation promotes dissociation of the α 2 β 2 tetramer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 For native Hb, the Ka of αβ dimers to α2β2 tetramer is reportedly 10 5 −10 6 M −1 . 23,46,47 Judging from the Ka values, the non-covalent interaction between αβ dimers has potential for application to construct a supramolecular polymer with DP > 10 at [M]0 > 1 mM. Actually, in the present SEC results of ββ-cross-linking at [M]0 = 1.00 mM (green chromatograms in Figure 4), CM-20 was efficiently ring-opened (r1 = 0.088) and polymerized to form XLSP-20 with a molecular size reaching to the column void volume (DP >10).…”
Section: Discussionmentioning
confidence: 99%